Plan de mercadeo para la empresa Oxford Centre de Ibagué (2021)
The changes that take place on a world scale, such as globalization, the intensification of competition, the acceleration of technological changes, the increasing demands of consumers or the search for excellence in institutions, have not left higher education on the sidelines . Changes are currently taking place in relations between the university and public administrations that aim to improve the efficiency of the institutions; But before a corporate only teaching the English language, it must prevail in many ways, because it is the international or world language for any event that you want to apply. The content presented in this project is aimed at people who wish to study the English language, before the corporate Oxford Center in the city of Ibague, knowingly, that it is emphasized in the face of current reality, that the English language is and continues being the international language, in every sense, business, study, and many other aspects. The approach that the project follows aims to develop communicative competence in students through activities in which language is used for specific purposes or purposes such as exchanging personal information, solving problems, learning more. The analysis of elements and linguistic rules appear in a contextualized way to favor observation and facilitate reflection; but the detailed notes for each level of teaching, provide suggestions to the tutor to deepen the development of said competence. Therefore marketing has become an essential factor.